The buy nothing, get everything plan : discover the joy of spending less, sharing more, and living generously - Clark, Liesl, 1966-; Rockefeller, Rebecca (Atria Books, 2020)
A powerful, environmentally-conscious guide to decluttering, saving money and growing a community inspired by the ancient practice of gift economies where neighbors pooled resources includes seven steps to learning how to buy less and give more.